Enhancing the competitive advantage for tourist souvenirs in Egypt: a marketing approach - Ali, Nour Elhoda; Mohamed, Ghada Abdallah; Alakhras, Hebatullah Atef (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The main aim of this research is to study the relationship between innovative marketing - in its various dimensions (innovation in product, innovation in price, innovation in promotion, innovation in distribution) - and enhancing the competitive advantage of tourist souvenirs in Egypt. Research methodology: The study adopted the descriptive-analytical approach for accurate and detailed descriptions of the study’s subject quantitatively and qualitatively and analyzed data available on this subject. The field study included surveying a random sample of tourists who frequented the souvenirs and handicrafts stores in various tourist cities in Egypt. Results: There is a statistically significant effect of innovative marketing in enhancing tourist souvenirs’ competitive advantage in Egypt. Overall findings highlighted that all the hypotheses were accepted. Limitations: The repercussions of the COVID-19 virus crisis reduced the scope of the study to only tourists in South Sinai and Red sea Governorates; whereas, tourist souvenirs stores were allowed to operate in accordance with the precautionary measures in only three main governorates: the Red Sea, South Sinai, and Marsa Matrouh, in addition to some gift shops in major hotels. Contribution: The study findings provide guidelines for practitioners within the tourist souvenirs and handicrafts sector to undertake the results and adapt them to assess and enhance their performance. Thus, they could improve their competitiveness. Keywords: Tourist souvenirs, Innovative marketing, Competitive advantage